2017
DOI: 10.1371/journal.pone.0188279
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care and opportunities for quality improvement of service provision in resource limited settings: A mixed methods study

Abstract: Antenatal care is essential to improve maternal and newborn health and wellbeing. The majority of pregnant women in Tanzania attend at least one visit. Since implementation of the focused antenatal care model, quality of care assessments have mostly focused on utilization and coverage of routine interventions for antenatal care. This study aims to assess the quality of antenatal care provision from a holistic perspective in a rural district in Tanzania. Structure, process and outcome components of quality are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 39 publications
4
76
2
1
Order By: Relevance
“…Maternity related community groups are shown to be generally supportive during pregnancy [40]. In India reported youth groups are undertaking activities to increase sensitization of maternal health problems and this improved maternal health outcomes [41]. Women who belonged to maternal health promoting clubs or groups during the antenatal period were found to be three times more likely to be birth prepared as compared with women without such clubs or groups.…”
Section: Predictors Of Bp/crmentioning
confidence: 99%
“…Maternity related community groups are shown to be generally supportive during pregnancy [40]. In India reported youth groups are undertaking activities to increase sensitization of maternal health problems and this improved maternal health outcomes [41]. Women who belonged to maternal health promoting clubs or groups during the antenatal period were found to be three times more likely to be birth prepared as compared with women without such clubs or groups.…”
Section: Predictors Of Bp/crmentioning
confidence: 99%
“…The World Health Organization predicts a world where every pregnant woman and newborn receives quality care throughout the pregnancy, childbirth, and the postnatal period (WHO, 2016a). There is widespread evidence that antenatal care (ANC) is very crucial in the reduction of maternal mortality and morbidity (Miltenburg et al, 2017;Sumankuuro et al, 2017). The recommendations of World Health Organization (WHO) on maternal health care promotion interventions encourage active male partner involvement in ANC delivery as well as postnatal care to improve upon the health outcome of both mothers and their children (WHO, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that although almost all facilities with ANC in Haiti and Malawi reported that they provided breastfeeding counseling as part of routine ANC services, less than 10% of clients received counseling on breastfeeding, regardless of trimester. Breastfeeding counseling is recommended for all pregnant women during ANC, but other studies have reported selective counseling during ANC due to low levels of provider Includes women who had at least one ANC visit, who delivered vaginally, and whose baby survived past the day of birth counseling knowledge and skills as well as heavy workloads [7,[51][52][53][54][55][56]. Breastfeeding counseling in Haiti and Malawi is likely hindered by the shortage of skilled health providers [24,25].…”
Section: Discussionmentioning
confidence: 99%